The role of crisis communication in crisis management in Algerian institution, a field study at the Eastern Construction and Urban Planning Corporation in M'Sila Province - herizi, abderraouf; ben aissa, ghusem (Journal of Social Sciences and Humanities, 2024)
This research paper sought to clarify the easiest ways in the process of employing crisis communication tools and techniques in Algerian institutions in order to contain damages and manage crises effectively by improving the institution’s communication strategies in dealing with the crisis and resolving it in a manner consistent with the developments occurring in the environment surrounding the institutions. The researcher used the descriptive approach to understand the crisis communication process and its role in managing crises in the East Construction and Urban Planning Institution in the state of M’Sila. He relied in his strategies to collect data on the phenomenon studied on the questionnaire tool, and concluded that crisis communication plays a vital and effective role in the process of managing crises and managing them in a way that leads to their resolution in the end. Communication, crisis communication, crises, crisis management, Algerian institution